Modifikasi dan Pengujian Alat Pengasapan Ikan Sistem Kabinet - Firna Bimantara; Agus Supriadi; Siti Hanggita (Universitas Sriwijaya, 2015)
The purposes of this research were to designed and to tested technically of the fish smoking closed cabinet system by using the wood as an energy resource and the coconut shell to smoked the snake fish which differenced for the semi conventional smoking cabinet. This research was done in two steps. There were the cabinet system productions’ step and the last is the testing of the cabinet system. The parameters observed is included fish temperature, smoking room temperature, the humidity smoking cabinet system, fish weight, moisture content, and the fuel. The result of the instrument made from the iron draft, wall of aluminium and the rack of stainless style has a good performance than the semi konventional cabinet system. For the time in smoked the snake fish (3.4 kg) on the smoking cabinet system needed 5–5.3 hours. Which the totally fuels are 11.5 kg of coconut shell and 5.57 kg the red wood is just than with the semi conventional cabinet system needed 10–12 hours and needed 21 kg of coconut shell and 15.5 of the red wood. The smoking cabinet system showed the smoking temperature profil is higher, RH is lower, the drying process with less the water contents on the fish which is faster than semi conventional cabinet system.